Transfer of Buddhism across Central Asian networks (7th to 13th centuries) - Meinert, Carmen. (Dynamics in the History of Religions, 2015)
The interdisciplinary volume Transfer of Buddhism across Central Asian Networks (7th to 13th Centuries) , edited by Carmen Meinert, offers a new transregional and transcultural vision for religious transfer processes in Central Asian history. It looks at the region as an integrated (religious) whole rather than from the perspective of fragmented sub-disciplines and analyses the spread of Buddhism as a driving force in a societal and cultural change of pan-Asian importance. One particular dimension of this 'Buddhist globalisation' was the rise of local forms of Buddhism. This volume explores Buddhist localisations through manuscripts and material culture in the multiethnic oases of the Tarim basin, the Transhimalyan region of Zangskar, Ladakh and Kashmir and the Western Tibetan Kingdom of Purang-Guge.